(untitled) (International Journal of Engineering and Computer Science, 2014)
Image fusion is about to combine the features of two or more partial occluded or damaged images to generate a new effective image. The proposed algorithm is about to improve the quality of CT image by using the concept of image fusion. In this work, an effective image analysis model is been presented under multiple parameters. The parameters that will be considered in this work are contrast analysis, entropy analysis and frequency analysis. The proposed algorithm begin, with the decomposition of images using DWT. These decomposed image parts will be analyzed using multiple parameters defined above. To perform the effective pixel area selection, the fuzzy logic will be applied. In this work, a two layered analysis is been performed for image fusion. The first level fusion will be done using DWT and second level fusion will be done using parametric fuzzy logic approach. As the presented work is defined on the basis of multiple parameters so that more effective results are expected from the defined approach. The work will be implemented in matlab environment. The obtained results shows the effective generation of fusion image. The analysis of work is done under different parameter that shows the work has improved the visibility of medical image.